Anti-inflammatory, Antioxidant, Lung and Liver Protective Activity of Galaxaura oblongata as Antagonistic Efficacy against LPS using Hematological Parameters and Immunohistochemistry as Biomarkers - Nabil-Adam, Asmaa; Shreadah, Mohamed A. (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2022)
Background: This study aimed to investigate the potential bioactivity and the ameliorative role of Galaxaura oblongata (G. oblongata) against LPS-induced toxicity using hematological parameters. Objective: The objective of this study is to examine its protective effect using the immunohistochemistry of the liver and lungs as biomarkers in male BALB/C albino mice. Materials and Methods: The current study was carried out using different in-vitro and in-vivo assays, such as phytochemicals, antioxidants and anti-inflammatory for in-vitro where the hematological and immunohistochemistry for lung and liver were investigated in vivo. Results: No previous studies were performed to investigate the in vivo and in vitro effects of the G. oblongata extracts as antioxidant and anti-inflammatory due to their rareness compared to other red algae. LPS treated mice revealed a significant decrease in the total number of WBCs, RBCs, platelets, and HGB%, MPV, MCV and MCHC compared to the control group. In contrast, the HCT and MCHC were increased in the induction group, which was treated with LPS compared to the control group. Furthermore, the immunohistochemistry results of the present study revealed the protective effect of G. oblongata compared to the induction group. G. oblongata can be used as protective marine natural products against the toxicity induced by LPS. Conclusion: It exhibited a significant ameliorative role against the alterations in the hematological parameters and immunohistochemistry of the liver and lungs, and reduced as well as coordinated the acute inflammations caused by TNF.
Keywords: hematological parameters